Acute effect of inhaled budesonide on bronchial inflammation in asthmatic rats - (:unkn) unknown (My University, 2001)
Although anti-inflammatory potency of inhaled corticosteroids is well established, little is known about their role in the acute phase. The aim of this study was to compare the acute anti-inflammatory effect of inhaled budesonide with systemic dexamethasone on allergen-induced inflammatory changes in asthmatic rats. Eighty-four Sprague Dawley rats were divided into four groups; group I (control, n = 24), group II (ovalbumin sensitized, n = 24), group III (systemic dexamethasone, n = 24), and group IV (budesonide, n = 12). All groups except group I were given ovalbumin aerosol challenges 14 days after sensitization with ovalbumin. The same procedure was applied to the control group using 0.9% saline. Group III received dexamethasane 0.3 mg/kg intraperitoneally and group IV received inhaled budesonide 1OmL (0.5 mg/mL) twice before the challenge. Eight hours after the challenge, bronchi of all the rats were evaluated for the degree of peribronchial inflammation. The most severe inflammation was seen in 8 of 24 rats (33%) in the second group, in 1 of 24 rats (4%) in the third group, and in 1 of 24 rats (4%) in the control group. None of the rats in group IV showed severe inflammation. No statistically significant difference was detected with respect to the presence of 3+ inflammation between the control vs. dexamethasone-, control vs. budesonide-, and dexamethasone vs. budesonide-receiving groups. Budesonide administration via nebulizer prior to exposure to an allergen may attenuate bronchial inflammation as effectively as systemic dexamethasone in rats.
Keywords: Acute; Asthma; Budesonide; Inflammation; Rats